(Aza)Pentacenes Clipped into a Ring: Stabilization of Large (Aza)Acenes. Issue 17 (3rd February 2021) - Ahrens, Lukas; Tverskoy, Olena; Weigold, Svenja; Ganschow, Michael; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: A doubly alkylene bridged 6, 13‐diphenylpentacene and analogously bridged azapentacenes were prepared; they are persistent. The doubly bridged azapentacenes display superior photochemical, oxidative and thermal stabilities compared to azapentacenes protected by bis(TIPS‐ethynyl)‐substituents—clipping an azaacene into a large ring is a viable complement in stabilization. Abstract : Doubly alkylene bridged tetraazahexacene and (aza)pentacenes were synthesized, introducing an alternative and complementary method of stabilization of large (hetero)acenes to trialkylsilylalkynylation. The examined materials display superior photochemical and thermal stabilities compared to their TIPS‐ethynyl substituted congeners.